The tender years - Oke, Janette, 1935- (Minneapolis, Minn. : Bethany House Publishers, 1997)
Marty and Clark's spiritual heritage has been lovingly passed on through the generations, and now their beloved granddaughter Virginia faces the test of her life, as she is caught in that difficult period between childhood and adulthood.
Accelerated Reader AR
Keywords: Christian fiction; Historical fiction